The safety and conspicuity of pedestrian crossing at roundabouts: The effect of median refuge island and zebra markings. (January 2020) - Vignali, Valeria; Pazzini, Margherita; Ghasemi, Navid; Lantieri, Claudio; Simone, Andrea; Dondi, Giulio
Highlights: A before–after speed analysis and a drivers' eye movement analysis were developed. The zebra markings and the median refuge island resulted the most glanced elements. The central island significantly lowered distractions in gaze behaviour for driver. Abstract: Roundabouts are one of the most used road intersections because, compared to signalized ones, they reduce conflict points between traffic flows and moderate driving speed. Great attention should also be paid to vulnerable road users at roundabouts. According to accident statistics, in fact, accessibility of pedestrians and cyclists is not always ensured. This paper has evaluated the effects on the visibility of pedestrian crossing before and after the displacement of zebra markings, moved before intersections, and the introduction of media refuge islands and "Yield here to pedestrians" vertical signs. The above effects have been assessed by before-after analysis of speed and visual behaviour of drivers approaching the crosswalk. Moreover, the analysis of the drivers' eye movements has highlighted the most salient elements of the pedestrian crossing. The relation between the drivers' visual behaviour and the vehicle speed have also been calculated. Results have confirmed that the intervention carried out has increased both visibility and safety of the studied pedestrian crosswalks. Zebra markings and the median refuge island have turned out to be the most glanced elements, respectively seen by 93.75% and 56.25% of the drivers, followed by the "Yield here to pedestrians" vertical sign. The mean distance of first fixation of the crosswalk increased from 21.98 m before the intervention, to 40.69 m after it. The drivers perceived the pedestrian crossings from a longer distance after the intervention, and they continued to glance at the crosswalk while approaching it, enhancing their visual attention.